Answer:
2 x² - 6x -5
Step-by-step explanation:
<u><em>Expansion:-</em></u>
Given that the expression
(8x²-7x-2)-(6x²-x+3)
= 8x² - 6x² - 7x +x -2 -3
= 2 x² - 6x -5
Answer: B?
Step-by-step explanation:
Since it already shows it in feet, you can multiply 18 by 16.
-288
And because it is $4.50 per square root, you can multiply 4.50 by 288 and you get 1,296.
(I don't really know tho..)
Answer:
1: 11982.79
2: 12136.31
4: 12216.09
12: 12270.46
365: 12297.10
Step-by-step explanation:
The compound interest formula is A=P*(1+r/n)^nt
P=principal amount
r=rate
n=number of compounds per period
t=number of periods
In this situation, the principal amount is 5,000=P. The rate is 6%, so r=0.06. n is equal to the top number in the table. And this is 15 years, so t=15.
For 1, it would be A=5,000*(1+.06/1)^1*15, or A=5,000(1.06^15), or 11982.79.
For 2, it would be 5,000*(1+.06/2)^2*15, or 5,000*(1.03^30), or 12136.31.
And so forth. Good luck
Answer:
$ 65.59 more per week
Step-by-step explanation:
Assuming she worked <u>52</u> weeks a year as a clerk :
30534 - <u> 52</u> * 521.6 = $ 3410.80 more per year
now each WEEK that is 3410.80 / 52 = 65.59
Answer: KJ becuase it is the first two like on but put backwards.